Assessing omega-3 intake in sport: the brief food frequency questionnaire and the omega-3 index in collegiate women soccer players - Essman, M.; Christifano, D.; Sullivan, D. K.; Chalise, P.; Carbuhn, A. (Journal of Athletic Training, 2022)
Context Omega-3 fatty acids modulate inflammatory processes and are considered beneficial for sport populations, highlighting a need to assess omega-3 intake in a practical manner. Food frequency questionnaires (FFQs) are inexpensive, noninvasive tools aimed at evaluating nutrient intakes such as omega-3 fatty acids. In healthy adults, a tailored, brief FFQ for estimating omega-3 intake was associated with the erythrocyte omega-3 fatty acid level, a biomarker for omega-3 tissue status and indicative of intake. However, the association between a brief omega-3 FFQ and erythrocyte levels, particularly the Omega-3 Index (eicosapentaenoic acid [EPA], docosahexaenoic acid [DHA], and EPA + DHA), has yet to be explored in a sport population.